ANTECEDENTS OF THE QUALITY OF GOVERNMENT FINANCIAL STATEMENT: THE ROLE OF REGIONAL ASSETS MANAGEMENT, INTERNAL CONTROL SYSTEMS, AND STAFF COMPETENCY - Banjarnahor, Doddy Chandra; Napitupulu, Ilham Hidayah; Nurlinda, Nurlinda (Kajian Akuntansi, 2024)
The aim of this research is to analyze the influence of the role of Regional Assets Management, Internal Control Systems, and Human Resource Competency on the Quality of Sibolga City Government Financial Reports. The method used in this study employs a quantitative approach; the data collection method uses a survey, and the data used are primary data (questionnaires). The total population in this study comprised 80 Sibolga City Government Regional Apparatus Organization Property Managers, comprising 30 Regional Apparatus Organization Property Administrators, 17 sub-district property administrators, 10 junior high school property administrators, and 23 elementary school property administrators. From the results of collecting the questionnaires, 46 questionnaires were obtained, which could be processed using SPSS software, version 25. The data analysis employed descriptive statistical data analysis, multiple linear regression techniques, and hypothesis testing. Based on the research results, it is shown that the Management of Regional Assets, Internal Control Systems, and Human Resource Competency have a positive and significant effect on the Quality of Financial Reports of the Sibolga City Government.   Keywords     : Human Resource Competence, Internal Control Systems, Management of Regional Assets, Quality of Financial Statement.